PENGEMBANGAN LOKALIN (LOKAL MALANG LEARNING) SEBAGAI MEDIA PEMBELAJARAN IPS KELAS VII DI SMP NEGERI 22 MALANG - Amalia, Rizky; Rohmah Adi, Khofifatu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study has aim to examine and made educational resources using Android mobile applications centered around local wisdom from Malang Raya, employing the ADDIE Research and Development (RandD) model. The process of developing the application includes generating content through Canva and PowerPoint, then transforming it into HTML5 format with iSpring Suite 11, and subsequently converting it into an Android application (APK) using Website 2 APK Builder Pro, allowing access on students' smartphones. Evaluation from subject matter experts and media specialists resulted in very favorable outcomes, scoring 87. 5% for content and 90% for media quality. Following revisions based on feedback from the validators, the media was utilized by seventh-grade students in class VII-C at SMPN 22 Malang, receiving a high approval rate of 94. 1%. This demonstrates that the media is highly suitable and effective for facilitating social studies lessons focusing on local wisdom from Malang Raya. The LOKALIN media enhances convenience and learning effectiveness, earning positive feedback from students. Therefore, this resource can serve as an innovative option for teaching local wisdom concepts in junior high schools.